Novel Role of miR-18a-5p and Galanin in Rat Lung Ischemia Reperfusion-Mediated Response. (17th August 2021) - Xiao, Kun; Song, Lei; Hu, Ye; He, Wanxue; Hou, Fei; Yan, Peng; Xu, Jianqiao; Wang, Kaifei; Tao, Yi; Li, Dan; Xie, Lixin
Abstract : Lung ischemia reperfusion (IR) is known to occur after lung transplantation or cardiac bypass. IR leads to tissue inflammation and damage and is also associated with increased morbidity and mortality. Various receptors are known to partake in activation of the innate immune system, but the downstream mechanism of tissue damage and inflammation is yet unknown. MicroRNAs (miRNAs) are in the forefront in regulating ischemia reperfusion injury and are involved in inflammatory response. Here, we have identified by high-throughput approach and evaluated a distinct set of miRNAs that may play a role in response to IR in rat lung tissue. The top three differentially expressed miRNAs were validated through quantitative PCRs in the IR rat lung model and an in vitro model of IR of hypoxia and reoxygenation exposed type II alveolar cells. Among the miRNAs, miR-18a-5p showed consistent downregulation in both the model systems on IR. Cellular and molecular analysis brought to light a crucial role of this miRNA in ischemia reperfusion. miR-18a-5p plays a role in IR-mediated apoptosis and ROS production and regulates the expression of neuropeptide Galanin. It also influences the nuclear localization of transcription factor: nuclear factor-erythroid 2-related factor (Nrf2) which in turn may regulate the expression of the miR-18a gene. Thus, we have not only established a rat model for lung IR and enumerated the important miRNAs involved in IR but have also extensively characterized the role of miR-18a-5p. This study will have important clinical and therapeutic implications for and during transplantation procedures.